Fabrication of a Band and Loop Space Maintainer - Elliot Shulman (Association of American Medical Colleges, 2011)
Abstract This resource is a video of the fabrication of a band and loop space maintainer on a dentaform. It includes instruction on fitting bands to teeth, taking a compound impression, bending wire, and soldering silver. It has greatly helped dental students visualize the steps required in fabricating a band and loop space maintainer. In addition, it has decreased the amount of faculty oversight required for the entire process while virtually eliminating unacceptable final products. Students learn the clinical situations where this appliance might be used and better anticipate the challenges in the fabrication/delivery and removal of the appliance. Faculty do not have to recreate/reproduce the preclinical session for students. Students can view/review this topic at their leisure prior to actual fabrication for a patient.